Prevalence of Intestinal Parasitic Infections among Schoolchildren of Kapan VDC, Kathmandu - KC, Upama; Rai, Shiva Kumar; Basnyat, Shaila; Upreti, Milan (International Journal of Applied Sciences and Biotechnology, 2019)
The present study investigated the intestinal parasitic infections in schoolchildren of Kapan VDC, Kathmandu, Nepal. A total of 330 schoolchildren were included in this study. Stool samples collected in clean, dry, screw-capped plastic containers were examined by formal-ether sedimentation technique. A total of 134 samples (40.6%) were positive for some kind of intestinal parasites. The percentage of monoparasitism (67.9%) were higher than multiparasitism (32.1%). Giardia lamblia (17.8%) and Trichuris trichiura (3.6%) were the commonest protozoa and helminthes respectively. Girls were marginally more infected (41.4%) than boys (39.8%) (p>0.05). Children 5 (41.5%) than ≤5 (40.1%) (p=0.82). In ethnic wise distribution, incidence rate of parasites was higher in Dalits (71.4%) and the least in Indo-Aryans (33.1%) (p